Emergent data influences the risk/benefit assessment of hemophilia gene therapy using recombinant adeno-associated virus - Puetz, John (Frontiers in Medicine, 2023)
After decades of investigation, gene therapy has received regulatory approval to treat hemophilia. However, since gene therapy investigations were initially conceived, other avenues of treatment have revolutionized the care of hemophilia. Emergent data is showing that gene therapy may not be as beneficial as hoped and more toxic than planned. At a minimum, a reassessment of risk/benefit estimate of gene therapy for hemophilia is needed.